2017
DOI: 10.1038/ncomms14498
|View full text |Cite
|
Sign up to set email alerts
|

Episodic release of CO2 from the high-latitude North Atlantic Ocean during the last 135 kyr

Abstract: Antarctic ice cores document glacial-interglacial and millennial-scale variability in atmospheric pCO2 over the past 800 kyr. The ocean, as the largest active carbon reservoir on this timescale, is thought to have played a dominant role in these pCO2 fluctuations, but it remains unclear how and where in the ocean CO2 was stored during glaciations and released during (de)glacial millennial-scale climate events. The evolution of surface ocean pCO2 in key locations can therefore provide important clues for unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 67 publications
2
30
0
Order By: Relevance
“…At sites where the carbonate system is strongly affected by seasonality and the fluxes of planktic foraminiferal tests have distinct seasonal patterns, the pH and thus pCO 2 estimates will likely be biased toward the season of maximum production. Also, since foraminifers calcify over a range of depths instead of strictly at the surface, the composite may be biased toward higher pCO 2 because seawater pCO 2 increases with depth within the top few hundreds of meters (Ezat et al, ; Raitzsch et al, ; Taylor et al, ; Yu et al, ). However, we found that these complexities would only have minor effects on our composite pCO 2 (Figures S6 and S7), probably because the calibrations that are largely based on core top measurements that already account for some of these effects.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…At sites where the carbonate system is strongly affected by seasonality and the fluxes of planktic foraminiferal tests have distinct seasonal patterns, the pH and thus pCO 2 estimates will likely be biased toward the season of maximum production. Also, since foraminifers calcify over a range of depths instead of strictly at the surface, the composite may be biased toward higher pCO 2 because seawater pCO 2 increases with depth within the top few hundreds of meters (Ezat et al, ; Raitzsch et al, ; Taylor et al, ; Yu et al, ). However, we found that these complexities would only have minor effects on our composite pCO 2 (Figures S6 and S7), probably because the calibrations that are largely based on core top measurements that already account for some of these effects.…”
Section: Resultsmentioning
confidence: 99%
“…The calibration used for Neogloboquadrina pachyderma ( N. pachyderma ) is δ 11 B borate = δ 11 B CaCO3 +3.38 ± 0.72‰ (first calibrated by Yu et al, , later confirmed by Gray, Weldeab, et al, over a wider range of pH). For the N. pachyderma JM11 record generated by NTIMS (Ezat et al, ), we used the original intercept of 2.053‰ (Ezat et al, , NTIMS) instead of 3.38‰ (Gray, Weldeab, et al, , MC‐ICP‐MS) to account for technique/machine offsets. Applying the T. sacculifer calibration curve to the Holocene δ 11 B of NIOP464 (Palmer et al, , NTIMS) and EDRC92 (Palmer & Pearson, , NTIMS) resulted in very different pH from the original publication, due to technique/machine offsets.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The present results find that after one millennium, in addition to the fast terrestrial release of carbon, the ocean accounts for an equal but more gradual release of CO 2 due to a combination of reduced biological activity, particularly in the Atlantic, and deep ocean ventilation in the Pacific sector of the Southern Ocean. While there is evidence of increased Southern Ocean upwelling during stadials (Anderson et al, ), recent ocean sediment δ 11 B results from the Nordic Seas support the possible release of carbon in the North Atlantic (Ezat et al, ).…”
Section: Discussionmentioning
confidence: 99%